2010
DOI: 10.4314/gjss.v8i2.51584
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality characteristics and gender on organizational citizenship behaviour

Abstract: This study investigated the influence of personality characteristics and gender on Organizational Citizenship Behaviour (OCB). One hundred and fifty (150) respondents comprising eighty (80) males and seventy (70) females were randomly drawn from the Ministries of Finance, Health, Lands and Survey; State Government Secretariat, Uyo, Akwa Ibom State. Their age range was between 20 and 50 years. The respondents were administered with a set of questionnaires comprising two sections (A & B). Section A was the (Eyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The study by Akinbode [33] did not show a positive association between some factors among participants, including age, gender, tenure, management level organization, demographic variables, and OCB. For example, Okediji et al [34] did not show any role for gender in OCB. Kim [35] showed that OCB does not depend on financial returns, but on the perception of employees of their personal values in their organization.…”
Section: Organizational Citizenship Behavior (Ocb)mentioning
confidence: 95%
“…The study by Akinbode [33] did not show a positive association between some factors among participants, including age, gender, tenure, management level organization, demographic variables, and OCB. For example, Okediji et al [34] did not show any role for gender in OCB. Kim [35] showed that OCB does not depend on financial returns, but on the perception of employees of their personal values in their organization.…”
Section: Organizational Citizenship Behavior (Ocb)mentioning
confidence: 95%
“…Every employee is expected to perform certain duties or tasks according to job specification, terms of employment and supervisors expectations. However, some individuals perform certain duties far beyond the expected outputs (Okediji et al, 2009). Some deliberately contribute to the progress and efficiency of the organization, while others go out of their way to motivate and assist their colleagues to complete their assigned tasks.…”
Section: Concept Of Organizational Citizenship Behaviormentioning
confidence: 99%
“…The study of Akinbode (2010) did not show a positive association between some factors including age, gender, tenure, management level organization, demographic variables, and (OCB) among participants. For example, Okediji, Esin, Sanni, and Umoh (2009) did not show any role for gender in (OCB). Kim (2009) showed that (OCB) does not depend on financial returns but on the perception of employees of their personal values in their organization.…”
Section: Introductionmentioning
confidence: 89%